PENINGKATAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK SMP MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Karimah, Imroatul; Jayati, Ariska Candra; Cahyono, Aprilian Dwi; Setiawan, Katon Galih; Rahmat, Ali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Problem Based Learning (PBL) learning model has become an interesting topic in education, especially in the context of improving 21st century learning skills, one of which is creative thinking skills. The purpose of the study was to determine the improvement of students' creative thinking skills through the application of the Problem Based Learning learning model in social studies subjects. The subjects of this study were students of class VIII G SMP Negeri 4 Jember consisting of 31 students who participated in social studies subjects with the application of the Problem Based Learning learning model. This type of research is a Collaborative Classroom Action Research (CCA) which is integrated with the independent learning practice cycle. The instrument used is a post test essay question. Data collection techniques using observation sheets made according to the syntax of the Problem Based Learning learning model. The technique of analyzing and interpreting students' creative thinking data refers to a modified scoring rubric. The results showed that the average creative thinking ability of students was 70,97% in cycle I, then an increase in cycle II of 84,37%. So that learning by using the Problem Based Learning model resulted in an increase in the percentage of creative thinking of VIIIGA class students by 13,40%.